1996
DOI: 10.1017/s0890037x00040963
|View full text |Cite
|
Sign up to set email alerts
|

Fluazifop-P Reduces Strawberry (Fragariaxananassa) Tolerance to Terbacil

Abstract: Greenhouse and field experiments were conducted to characterize a synergistic interaction between fluazifop-P and terbacil in strawberry (FragariaxananassaDuchesne). In the greenhouse, injury from foliar terbacil applications generally increased two- or more fold when 75 or 150 g/ha fluazifop-P was applied foliarly 24 h later to either a terbacil tolerant (‘Veestar’) or sensitive (‘Kent’) strawberry cultivar. Synergism also occurred when terbacil was applied as a soil drench and fluazifop-P was applied 5 d lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Data from this experiment confi rm previous studies showing strawberry cultivars vary in their tolerance to terbacil (Jensen et al, 1996;Lindstrom and Swartz, 1987;Masiunas and Weller, 1986;Weller, 1984). In this experiment, 'Jewel' was less tolerant to applications of terbacil than was 'Mira', but similar in tolerance to 'Allstar' based on visual injury.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Data from this experiment confi rm previous studies showing strawberry cultivars vary in their tolerance to terbacil (Jensen et al, 1996;Lindstrom and Swartz, 1987;Masiunas and Weller, 1986;Weller, 1984). In this experiment, 'Jewel' was less tolerant to applications of terbacil than was 'Mira', but similar in tolerance to 'Allstar' based on visual injury.…”
Section: Discussionsupporting
confidence: 86%
“…In our study 'Jewel' was more vigorous based on leaf dry weight but was damaged more severely by terbacil than the slower-growing cultivar 'Mira', refuting Masiunas and Weller (1986). However, strawberries have been shown to completely outgrow moderate foliar injury of terbacil within a few months (Jensen et al, 1996). It is likely that these plants would have responded in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that fluazifop-P and terbacil interact synergistically in strawberry (Jensen et al 1996). When applied alone, strawberry plants have a high tolerance of fluazifop-P, even when applied repeatedly at high rates (Clay et al 1990) and during sensitive crop stages like bloom (Doohan et al 1986).…”
Section: Introductionmentioning
confidence: 99%